The Impact of K-POP Culture in Student in Teacher View - Bahagia Bahagia; Leny Muniroh; Abdul Karim Halim; Rimun Wibowo; Azhar Al Wahid; Muhammad Shiddiq Ilham Noor; Tiwi Siswanti; Rizkal Rizkal (Universitas Pahlawan Tuanku Tambusai, 2022)
K-POP culture is not native to Indonesia but comes from Korea. This study aims to determine the impact of K-Pop culture on the behavior of school children from the teacher's point of view. This research uses the descriptive qualitative method. Meanwhile, respondents were selected by using a purposive technique, namely setting a sample with various considerations. This study chose teachers as respondents. The results showed the spread of K-pop culture through social media such as Facebook and Instagram and the world of digitalization such as Tik-Tok. Friends also influence the spread of K-pop because other friends will follow the behavior of their friends. Then, K-pop culture has the potential to erode local culture such as angklung and jaipongan in Sundanese society because generations of school children can prefer K-pop culture. This condition is influenced by the role of parents. When parents are literate in Sundanese local culture and make that culture into life behavior, the children at home will follow the example. Likewise in schools, when schools instill local culture, school children will participate in that culture. Simultaneously, the community environment supports local culture, so there will be filtration of culture from abroad. But it is not wrong to learn about other cultures. K-pop also generates economic value because salons as a place to change hairstyles will sell well, and Korean-style fashion will also sell and grow Korean food and beverage cuisine